Precocious transitions and long-term heroin use outcomes: A longitudinal study of gang-affiliated Mexican-American males - Cepeda, Alice (Addict Behav, 2016)
A longitudinal study (15 years) investigates heroin use patterns following precocious transition experiences for gang-affiliated Mexican-American males (n=119) in San Antonio, Texas. Five precocious transitions are examined: cohabitation, early nest leaving, school dropout, teenage parenthood, and unemployment (while not in school). Half of these men used heroin over the follow-up period for an average of under 4 years. Findings from a zero-inflated Poisson model indicate that while these transitions do not have a significant effect on initiation of heroin use, they do have an important influence on individual's drug trajectories once they have initiated. Early-nest leaving and teenage parenthood are protective factors for continued heroin use while dropping out of high school and cohabiting during this same period are risk factors. Findings are discussed within the context of these disadvantaged and marginalized communities.